Characteristic Test and Antihyperuricemia Activity of Ethanol Extract Stem of Etlingera rubroloba A.D Poulsen In vitro - Asriullah Jabbar; Idin Sahidin; Khansa Rafida Triaqilah; Mubarak Mubarak; Muhammad Ilyas Yusuf (Halu Oleo University, 2022)
Background: Etlingera rubroloba (E. rubroloba) A.D Poulsen is one of the endemic plants of Southeast Sulawesi, which has the largest species in the world. Local people widely use this plant as traditional medicine. Many of these plant species have been previously reported as antioxidants, antibacterials, and others. However, for E. rubroloba, there are still very few reports from a pharmacological aspect, especially anthiperuricemia. Objective: This study was conducted to determine the characteristics and activity of the ethanol extract of the stem of E. rubroloba A.D Poulsen in vitro. Methods: The stems of E. rubroloba A.D Poulsen were extracted with ethanol solvent by maceration, then the filtrate obtained was evaporated using an evaporator to get an ethanol extract. Furthermore, the extract characterization test was carried out, including water content, ash content, water-soluble extract content, and ethanol-soluble extract content. Then the antihyperuricemia activity test in vitro using the Xanthine Oxidase (XO) kit. Results: The results of the characteristic test showed that the ethanolic extract of E. rubroloba contained 5.15% water content, 5.485% ash content, 55.2% water-soluble extract content, and 56.52% ethanol-soluble extract content. Furthermore, the antihyperuricemic activity of the ethanol extract of E. rubroloba was IC50 48.59 ± 0.03 g/mL and Allopurinol 42.21 ± 0.02 g/mL as positive controls. Conclusion: E. rubroloba stem ethanol extract has characterization results according to the literature, has antihyperuricemia activity, and is a reference for the development of traditional drugs